2022
DOI: 10.3390/agronomy12051130
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Grain Yield Stability in Some Selected Wheat Genotypes Using AMMI and GGE Biplot Methods

Abstract: Wheat Triticum aestivum L. is one of the most important agricultural products, and meets the highest nutritional needs of humans in various countries. This study aims to evaluate the compatibility and stability of 25 wheat genotypes for two crop years in five regions (Karaj, Qazvin, Isfahan, Varamin and Damavand) in a randomized complete block design with three replications. The results of variance analysis in the additive main effects and multiplication interaction (AMMI) method showed that the effect of geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 21 publications
1
18
0
Order By: Relevance
“…Many investigations have assessed wheat genotypes and the AMMI model has been specified for proper identification of genotypes with general and specific adaptability to diverse environments [ 86 ]. In this study, stability evaluation of 17 varieties and lines of hexaploid amphiploid with the multivariate method of AMMI showed that tritipyrum and triticale lines had more stability and adaptability than Iranian wheat varieties.…”
Section: Resultsmentioning
confidence: 99%
“…Many investigations have assessed wheat genotypes and the AMMI model has been specified for proper identification of genotypes with general and specific adaptability to diverse environments [ 86 ]. In this study, stability evaluation of 17 varieties and lines of hexaploid amphiploid with the multivariate method of AMMI showed that tritipyrum and triticale lines had more stability and adaptability than Iranian wheat varieties.…”
Section: Resultsmentioning
confidence: 99%
“…GY is a quantitative trait determined by the additive main effect of environment (E) and genotype (G) in addition to the nonadditive effect of the G X E interaction (GEI) [ 9 ]. Breeders focus on the GEI effect to identify the yield stability of genotypes across different conditions and environments, which cannot be revealed by the separate effects of genotype or environment [ 10 , 11 , 12 , 13 , 14 ]. The GY heritability is exposed to variability across different environments [ 15 , 16 ], which hinders the accuracy of superior varietal selection processes [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Different statistical procedures are used to explore the stability of assessed genotypes such as Additive main effects and multiplicative interaction (AMMI) ( Gauch, 1992 ), joint regression ( Eberhart and Russell, 1966 ), Wricke’s Ecovalence ( Wricke, 1962 ), and Cultivar superiority ( Lin and Binns, 1988 ). Several researchers assessed the phenotypic stability of yield performance using different statistical procedures and deduced different stability degrees across multi-environment trials ( Mansour et al., 2018a ; Alipour et al., 2021 ; Awaad, 2021 ; Omrani et al., 2022 ). Although several studies assessed yellow rust resistance, heat tolerance, agronomic performance, and yield stability of wheat genotypes severally, additional investigation is needed to assess these biotic and abiotic stresses alongside the agronomic performance.…”
Section: Introductionmentioning
confidence: 99%